2015
DOI: 10.2147/ijn.s81201
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of total β-subunit of human chorionic gonadotropin concentration in urine by immunomagnetic reduction to assist in the diagnosis of ectopic pregnancy

Abstract: Background The initial diagnosis of ectopic pregnancy depends on physical examination, ultrasound, and serial measurements of total β-subunit of human chorionic gonadotropin (hCGβ) concentrations in serum. The aim of this study was to explore the possibility of using quantitative analysis of total hCGβ in urine rather than in serum by immunomagnetic reduction (IMR) assay as an alternative method to diagnose an ectopic pregnancy. Methods We established a standard calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In addition to proteins, IMR has also been applied for the sensing of small molecules like hormones, as it has been reported by Chen et al for the detection of the β-subunit of human chorionic gonadotropin in urine samples of pregnant women [ 165 ]. Furthermore, a general proof for the successful detection of DNA by IMR measurements can be found in the publication of Yang et al [ 166 ].…”
Section: Magnetic Detection Methodsmentioning
confidence: 99%
“…In addition to proteins, IMR has also been applied for the sensing of small molecules like hormones, as it has been reported by Chen et al for the detection of the β-subunit of human chorionic gonadotropin in urine samples of pregnant women [ 165 ]. Furthermore, a general proof for the successful detection of DNA by IMR measurements can be found in the publication of Yang et al [ 166 ].…”
Section: Magnetic Detection Methodsmentioning
confidence: 99%
“…We can see that the RRS analytical system is more sensitive than the Abs and was thus chosen for sample detection. Compared to the reported hCG methods, [25][26][27][28][29][30][31][32][33][34][35][36] this RRS method is not only sensitive and selective but also facile, of low-cost and without nanoparticle aggregation. The clinical method of chemiluminescent immunoassay had a DL of 0.143 ng/mL, limit of quantitation (LQ) of 5 ng/mL and linear range of 5-540 ng/mL hCG; 37 the DL and LQ of this RRS method are better than the clinical method, and the linear range of the two methods are close to each other, as the upper LQ divided by the lower LQ is 108 and 100, respectively.…”
Section: Working Curvementioning
confidence: 99%
“…Recently, some new assays were developed for the detection of hCG. [31][32][33][34][35][36] Zhao et al 31 reported a microplate magnetic chemiluminescence enzyme immunoassay for the determination of hCG using the alkaline phosphatase (ALP) as a labeled reagent and 3-(2′-spiroadamantane)-4-methoxy-4-(3″-phosphoryloxy) phenyl-1,2-dioxetane (AMPPD) as a chemiluminescence reagent. Chang et al 32 combined catalytic gold nanoparticles with an hCG-specific peptide aptamer to create a simple, sensitive, label-free colorimetric assay for hCG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular biomarkers are often but not always linked with less invasive sampling, for example the withdrawal of a peripheral venous blood sample or urine collection. Examples are urine test for beta-human chorionic gonadotrophin (Chen et al, 2015 ) as an indicator of pregnancy or prostate specific antigen (PSA) (Ravery, 1999 ) in a suspected prostate cancer case.…”
mentioning
confidence: 99%